FINANCIAL FIRM PRODUCTION OF INSIDE MONETARY AND CREDIT CARD SERVICES: AN AGGREGATION THEORETIC APPROACH. (23rd November 2018) - Barnett, William A.; Su, Liting
Abstract : A monetary production model of financial firms is employed to investigate supply-side inside-money aggregation, augmented to include credit card transaction services. Inside money is a supply-side concept. Financial firms are conceived to produce monetary and credit card transaction services as outputs through financial intermediation. While credit cards provide transactions services, credit cards have never been included into measures of the money supply. The reason is accounting conventions, which do not permit adding liabilities to assets. However, index number theory measures service flows and is based on microeconomic aggregation theory, not accounting. We derive theory needed to measure the supply of the joint services of credit cards and inside money, needed to estimate the output supply function and to compute value added. The data needed for empirical implementation of our theory are available online from the Center for Financial Stability in New York City.